Gas barrier laminate and packaging bag
Patent Information
- Application Number
- JP2024561590
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-06-16
- Filing Date
- 2024-06-14
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2044-06-14
AI Technical Summary
【0017】 本開示によれば、レトルト処理後においてもガスバリア性を良好に発揮可能なガスバリア積層体及び包装袋を提供できる。
Smart Images

Figure 0007632775000014 
Figure 0007632775000015 
Figure 0007632775000016
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a gas barrier laminate and a packaging bag. [Background technology]
[0002] Conventionally, laminates (gas barrier laminates) provided with gas barrier properties such as oxygen barrier property and water vapor barrier property have been used from the viewpoint of protecting contents wrapped in packaging materials. For example, Patent Document 1 below discloses a gas barrier laminate film including a resin substrate, a gas barrier deposition layer provided on the resin substrate and mainly containing an inorganic compound, and a gas barrier coating layer provided on the gas barrier deposition layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4200972 Summary of the Invention [Problem to be solved by the invention]
[0004] When the gas barrier laminate as described above is subjected to a retort treatment, there is a problem that the gas barrier properties are easily deteriorated.
[0005] An object according to one aspect of the present disclosure is to provide a gas barrier laminate and a packaging bag that are capable of exhibiting good gas barrier properties even after retort treatment. [Means for solving the problem]
[0006] A gas barrier laminate according to one aspect of the present disclosure comprises a barrier layer having a substrate on which a barrier coat is provided, a sealant layer overlying a first main surface of the barrier layer, a support layer overlying a second main surface of the barrier layer, a first adhesive layer bonding the barrier layer and the sealant layer together, and a second adhesive layer bonding the barrier layer and the support layer together, wherein the first adhesive layer comprises a two-component curing urethane adhesive, the substrate comprises a polyolefin, and after retort treatment is performed on the gas barrier laminate, the elastic modulus of the first adhesive layer measured with a scanning probe microscope is 5 MPa or more and less than 53 MPa.
[0007] According to this gas barrier laminate, the elastic modulus of the first adhesive layer measured by a scanning probe microscope (SPM) is 5 MPa or more and less than 53 MPa. In this case, even if the base material expands and contracts due to the retort treatment, the first adhesive layer follows it well. Therefore, damage to the barrier coat due to cracks in the first adhesive layer can be suppressed. Therefore, it is possible to provide a gas barrier laminate that can exhibit good gas barrier properties even after the retort treatment.
[0008] The second adhesive layer includes a two-component curing urethane adhesive, and the modulus of elasticity of the second adhesive layer measured by a scanning probe microscope after the retort treatment may be 5 MPa or more and less than 53 MPa. In this case, even if the base material and the support layer expand and contract due to the retort treatment, the second adhesive layer follows well. Therefore, damage to the barrier coat due to cracks in the second adhesive layer can be suppressed.
[0009] The barrier layer may further include an anchor coat layer and a deposition layer located between the substrate and the barrier coat, and the anchor coat layer may be located between the substrate and the deposition layer. In this case, the gas barrier properties of the gas barrier laminate can be improved.
[0010] The thickness of the vapor-deposited layer may be 5 nm or more and 80 nm or less, which can improve the gas barrier properties while preventing cracks in the vapor-deposited layer.
[0011] Before the retort treatment, the first adhesive layer may have an elastic modulus of 55 MPa or more as measured by a scanning probe microscope.
[0012] The thickness of the first adhesive layer and the thickness of the second adhesive layer may each be 0.5 μm or more and 10 μm or less, in which case the gas barrier laminate can be easily made into a mono-material while effectively suppressing peeling between the barrier layer and the sealant layer.
[0013] The elastic modulus of the sealant may be 600 MPa or more and 1400 MPa or less, in which case the moldability of the gas barrier laminate may be improved.
[0014] The substrate and the sealant layer may each be a polyolefin film, and the total mass ratio of polyolefin in the gas barrier laminate may be 90 mass % or more. In this case, mono-material construction is realized.
[0015] The substrate may be a stretched polypropylene film and the sealant layer may be a non-stretched polypropylene film, in which case the laminate has excellent heat resistance against retort treatment and the like.
[0016] One aspect of the present disclosure may provide a packaging bag which is a bag made of the gas barrier laminate. Effect of the Invention
[0017] According to the present disclosure, it is possible to provide a gas barrier laminate and a packaging bag that are capable of exhibiting good gas barrier properties even after retort treatment. [Brief description of the drawings]
[0018] [Figure 1] FIG. 1 is a schematic plan view of a laminate according to one embodiment. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing a laminate according to one embodiment. [Diagram 3] FIG. 3 is a schematic front view of an example of a packaging bag. [Figure 4]FIG. 4 is a schematic diagram showing a method for measuring the thermal shrinkage rate during heating in an oven. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Hereinafter, preferred embodiments of the present disclosure will be described in detail with reference to the drawings as needed. In the drawings, the same or corresponding parts are denoted by the same reference numerals, and duplicated explanations will be omitted. In addition, the dimensional ratios of the drawings are not limited to the ratios shown in the drawings.
[0020] <Laminate> Fig. 1 is a schematic plan view of a laminate according to one embodiment. Fig. 2 is a schematic cross-sectional view of a laminate according to one embodiment. The laminate 1 shown in Figs. 1 and 2 is a sheet-like member (gas barrier laminate) having gas barrier properties, and is, for example, a sheet-like packaging material used in the manufacture of packaging bags and the like. The laminate 1 can be suitably used in applications where a heat treatment such as a retort treatment or a boiling treatment is performed.
[0021] Retort processing is a method of sterilizing microorganisms such as mold, yeast, and bacteria under pressure to preserve foods, medicines, etc. Usually, a packaging bag containing food, etc. is sterilized under pressure at 105-140°C, 0.15-0.30 MPa, and 10-120 minutes. There are two types of retort devices: a steam type that uses heated steam and a hot water type that uses pressurized heated water, and they are used appropriately depending on the sterilization conditions of the food, etc. that will be the contents. Boiling processing is a method of sterilizing with moist heat to preserve foods, medicines, etc. Usually, depending on the contents, a packaging bag containing food, etc. is sterilized with moist heat at 60-100°C, atmospheric pressure, and 10-120 minutes. Boiling processing is usually performed using a hot water bath at 100°C or less. There are two types of methods: a batch type in which the bag is immersed in a hot water bath at a constant temperature and treated for a certain period of time, and then removed, and a continuous type in which the bag is passed through a hot water bath in a tunnel-like manner.
[0022] The laminate 1 has a barrier layer 10, a sealant layer 20, a first adhesive layer 30, a support layer 40, and a second adhesive layer 50. In the laminate 1, the sealant layer 20, the first adhesive layer 30, the barrier layer 10, the second adhesive layer 50, and the support layer 40 are laminated in this order. In the following, as shown in Fig. 1, the direction MD is defined as the flow direction (longitudinal direction) of the laminate 1, and the direction TD is defined as the width direction (short direction) of the laminate 1. In addition, the direction perpendicular to both directions MD and TD is defined as the stacking direction of the members included in the laminate 1.
[0023] [Barrier layer 10] The barrier layer 10 is a member that functions as an intermediate layer in the laminate 1, and exhibits gas barrier properties against gases such as water vapor and oxygen. As shown in FIG. 2, the barrier layer 10 has a substrate 11, an adhesion layer 12, a deposition layer 13, and a barrier coat 14. In the barrier layer 10, the substrate 11, the adhesion layer 12, the deposition layer 13, and the barrier coat 14 are laminated in this order. Therefore, the adhesion layer 12 and the deposition layer 13 are located between the substrate 11 and the barrier coat 14 in the stacking direction, and the adhesion layer 12 is located between the substrate 11 and the deposition layer 13. In this embodiment, the substrate 11 of the barrier layer 10 is closest to the first adhesive layer 30 in the stacking direction and forms the first main surface 10b of the barrier layer 10. Therefore, the barrier coat 14 of the barrier layer 10 is farthest from the first adhesive layer 30 in the stacking direction and forms the second main surface 10a of the barrier layer 10.
[0024] [Base material 11] The substrate 11 is a plastic member that functions as a support layer in the laminate 1. The thickness of the substrate 11 is not particularly limited. Depending on the application, the thickness can be set to 6 to 200 μm, but from the viewpoint of reducing materials to reduce the environmental load and from the viewpoint of obtaining excellent heat resistance, impact resistance, and excellent gas barrier properties, the thickness may be 9 to 50 μm, 12 to 38 μm, or 18 to 30 μm.
[0025] From the viewpoint of recycling suitability of the laminate 1, the base material 11 is, for example, a polyolefin film. In this embodiment, the base material 11 may contain a polypropylene film or may be made of a polypropylene film. The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. In addition, as the polypropylene, a polypropylene-based resin such as a homopolypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, or a propylene-α-olefin copolymer may be used.
[0026] The polypropylene film constituting the substrate 11 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.
[0027] The polypropylene film constituting the substrate 11 may be a stretched film or a non-stretched film. From the viewpoints of impact resistance, heat resistance, water resistance, dimensional stability, and the like, the polypropylene film may be a stretched polypropylene film. This can prevent the substrate 11 from being thermally fused in the heat sealing process during bag making. The laminate 1 may also be used for applications in which a heat treatment such as a retort treatment or a boiling treatment is performed. The stretching method is not particularly limited, and any method may be used as long as a dimensionally stable film can be provided, such as stretching by inflation, uniaxial stretching, or biaxial stretching.
[0028] The laminated surface of the substrate 11 may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or may be provided with a coating layer such as an easy-adhesion layer, as long as the pretreatment does not impair the barrier performance. The laminated surface may be the surface that forms the first main surface 10b of the barrier layer 10.
[0029] [Thermal shrinkage rate of base material 11] After the substrate 11 is exposed to 120°C for 15 minutes (hereinafter simply referred to as "after heating"), the heat shrinkage rate in the MD direction of the substrate 11 calculated by the following formula (1) is 1% or more. For example, after the substrate 11 or the barrier layer 10 including the substrate 11 is heated in an oven at 120°C for 15 minutes, the heat shrinkage rate in the MD direction of the substrate 11 calculated by the following formula (1) is 1% or more. From the viewpoints of reducing deformation during bag making and suppressing peeling between the barrier layer 10 and the sealant layer 20, the heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, etc. In one example, the heat shrinkage rate in the MD direction is 1.2% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, etc. The heat shrinkage rate in the MD direction is, for example, 1% or more and 7% or less, 1% or more and 6.7% or less, 1.5% or more and 4% or less, 2% or more and 3.7% or less, etc. For example, the heat shrinkage rate of a biaxially oriented polypropylene film is 1%, whereas the heat shrinkage rate of a PET film is less than 1%. Thermal shrinkage rate in MD direction (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)
[0030] After the heating, the heat shrinkage rate in the TD direction of the substrate 11 calculated by the following formula (2) is not particularly limited, but is, for example, 1% or more and is equal to or less than the heat shrinkage rate in the MD direction of the substrate 11. From the viewpoints of reducing deformation during bag making and suppressing peeling between the barrier layer 10 and the sealant layer 20, the heat shrinkage rate in the TD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, 7% or less, etc. In one example, the heat shrinkage rate in the TD direction is 1.2% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, etc. The heat shrinkage rate in the TD direction is, for example, 1% or more and 7% or less, 1% or more and 6.7% or less, 1.5% or more and 4% or less, 2% or more and 3.7% or less, etc. Thermal shrinkage rate in TD direction (%) = (length in TD direction before heating - length in TD direction after heating) / length in TD direction before heating × 100 ... (2)
[0031] Generally, in a stretched film such as a biaxially stretched film, the heat shrinkage in the MD direction is greater than the heat shrinkage in the TD direction.
[0032] [Adhesion layer] The adhesion layer 12 functions as a layer (anchor coat layer) capable of improving the adhesion performance of the deposition layer 13 on the substrate 11, and is provided directly on the substrate 11. For this reason, the adhesion layer 12 is located between the substrate 11 and the deposition layer 13. By providing the adhesion layer 12, the smoothness of the surface of the barrier layer 10 on which the deposition layer 13 is provided can be improved. Note that improved smoothness makes it easier to form the deposition layer 13 uniformly without defects, and makes it easier to exhibit high barrier properties. The adhesion layer 12 can be formed, for example, using an anchor coat agent.
[0033] Examples of the anchor coating agent include polyester-based polyurethane resins, polyether-based polyurethane resins, etc. As the anchor coating agent, polyester-based polyurethane resins may be used from the viewpoints of heat resistance and interlayer adhesive strength.
[0034] The thickness of the adhesive layer 12 is not particularly limited, and may be in the range of 0.01 to 5 μm, 0.03 to 3 μm, or 0.05 to 2 μm. If the thickness of the adhesive layer 12 is equal to or greater than the lower limit, a more sufficient interlayer adhesive strength tends to be obtained, whereas if the thickness is equal to or less than the upper limit, a desired gas barrier property tends to be easily exhibited.
[0035] As a method for applying the adhesive layer 12 onto the substrate 11, known application methods can be used without any particular limitation, and examples thereof include a dipping method, a method using a spray, a coater, a printer, a brush, etc. In addition, examples of the types of coaters and printers used in these methods and the application methods thereof include gravure coaters such as direct gravure method, reverse gravure method, kiss reverse gravure method, and offset gravure method, reverse roll coaters, microgravure coaters, coaters combined with chamber doctor, air knife coaters, dip coaters, bar coaters, comma coaters, die coaters, etc.
[0036] The coating amount of the adhesive layer 12 is 1 m after the anchor coating agent is applied and dried. 2 Mass per unit is 0.01 to 5 g / m 2 or 0.03 to 3 g / m 2 It is also acceptable. 1m after applying and drying the anchor coating agent 2 When the mass per unit area is equal to or greater than the lower limit, the film tends to be sufficiently formed, whereas when the mass per unit area is equal to or less than the upper limit, the film tends to be sufficiently dried and the solvent is less likely to remain.
[0037] The method for drying the adhesive layer 12 is not particularly limited, but examples thereof include a method of natural drying, a method of drying in an oven set at a predetermined temperature, and a method using a dryer attached to the coater, such as an arch dryer, a floating dryer, a drum dryer, an infrared dryer, etc. Furthermore, the drying conditions can be appropriately selected depending on the drying method, and for example, in a method of drying in an oven, drying may be performed at a temperature of 60 to 100° C. for about 1 second to 2 minutes.
[0038] A polyvinyl alcohol resin can be used instead of the polyurethane resin as the adhesive layer 12. The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit obtained by saponifying a vinyl ester unit, and examples of the polyvinyl alcohol resin include polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH).
[0039] Examples of PVA include resins obtained by homopolymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, followed by saponification. PVA may be modified PVA that has been copolymerized or post-modified. Modified PVA can be obtained, for example, by copolymerizing a vinyl ester with an unsaturated monomer copolymerizable with the vinyl ester, followed by saponification. Examples of unsaturated monomers copolymerizable with vinyl ester include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-buten-1-ol, 4-pentyn-1-ol, and 5-hexen-1-ol; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; nitriles such as acrylonitrile and methacrylonitrile; diacetone acrylamide, acrylonitrile, methacrylonitrile, and methacrylonitrile; and the like. amides such as arylamide and methacrylamide; olefin sulfonic acids such as ethylene sulfonic acid, allyl sulfonic acid, and methallyl sulfonic acid; vinyl compounds such as alkyl vinyl ethers, dimethylallyl vinyl ketone, N-vinylpyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxane, glycerin monoallyl ether, and 3,4-diacetoxy-1-butene; vinylidene chloride, 1,4-diacetoxy-2-butene, and vinylene carbonate.
[0040] The polymerization degree of PVA is, for example, 300 to 3000. If the polymerization degree is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The saponification degree of PVA may be 90 mol% or more, 95 mol% or more, or 99 mol% or more. The saponification degree of PVA may be 100 mol% or less, or 99.9 mol% or less. The polymerization degree and saponification degree of PVA can be measured in accordance with the method described in JIS K 6726 (1994).
[0041] EVOH is generally obtained by saponifying a copolymer of ethylene and a vinyl ester such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, or vinyl versatate.
[0042] The degree of polymerization of EVOH is, for example, 300 to 3000. If the degree of polymerization is less than 300, the barrier property is likely to decrease, and if it exceeds 3000, the viscosity is too high and the coating suitability is likely to decrease. The degree of saponification of the vinyl ester component of EVOH may be 90 mol% or more, 95 mol% or more, or 99 mol% or more. The degree of saponification of EVOH may be 100 mol% or less, or 99.9 mol% or less. The degree of saponification of EVOH is determined by performing nuclear magnetic resonance (1H-NMR) measurement and measuring the peak area of hydrogen atoms contained in the vinyl ester structure and the peak area of hydrogen atoms contained in the vinyl alcohol structure.
[0043] The ethylene unit content of EVOH is 10 mol% or more, more preferably 15 mol% or more, even more preferably 20 mol% or more, and particularly preferably 25 mol% or more. The ethylene unit content of EVOH is preferably 65 mol% or less, more preferably 55 mol% or less, and even more preferably 50 mol% or less. When the ethylene unit content is 10 mol% or more, the gas barrier property or dimensional stability can be maintained well under high humidity. On the other hand, when the ethylene unit content is 65 mol% or less, the gas barrier property can be improved. The ethylene unit content of EVOH can be determined by NMR method.
[0044] When a polyvinyl alcohol resin is used as the adhesive layer 12, the adhesive layer 12 can be formed by coating a polyvinyl alcohol resin solution, multi-layer extrusion, or the like.
[0045] [Vapour-deposited layer 13] The deposition layer 13 is a layer (gas barrier layer) that exhibits gas barrier properties against water vapor and oxygen, and contains at least one of a metal and an inorganic oxide. The deposition layer 13 is provided directly on the adhesive layer 12. The deposition layer 13 may have a single-layer structure or a laminated structure. Therefore, the deposition layer 13 contains at least one of a metal deposition layer and an inorganic oxide layer. When the deposition layer 13 includes a metal deposition layer, examples of the metal contained in the metal deposition layer include aluminum and stainless steel. When the deposition layer 13 includes an inorganic oxide layer, examples of the inorganic oxide contained in the inorganic oxide layer include aluminum oxide, silicon oxide, magnesium oxide, and tin oxide. From the viewpoint of transparency and barrier properties, the inorganic oxide may be selected from the group consisting of aluminum oxide, silicon oxide, and magnesium oxide. In addition, from the viewpoint of excellent tensile stretchability during processing, the inorganic oxide layer may contain a layer using silicon oxide. By using an inorganic oxide layer, high barrier properties can be obtained with a very thin layer within a range that does not affect the recyclability of the laminate 1.
[0046] When the deposition layer 13 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer is preferably 1.7 or more. When the O / Si ratio is 1.7 or more, the content ratio of metal Si is suppressed, and good transparency is easily obtained. In addition, the O / Si ratio is preferably 2.0 or less. When the O / Si ratio is 2.0 or less, the crystallinity of SiO is high, and the inorganic oxide layer can be prevented from becoming too hard, and good tensile resistance is obtained. This makes it possible to suppress the occurrence of cracks in the inorganic oxide layer when laminating the barrier coat 14. In addition, even after forming into a packaging bag, the substrate 11 may shrink due to heat during boiling or retort treatment, but when the O / Si ratio is 2.0 or less, the inorganic oxide layer easily follows the above shrinkage, and the deterioration of the barrier property can be suppressed. From the viewpoint of obtaining these effects more fully, the O / Si ratio of the inorganic oxide layer is preferably 1.75 to 1.9, and more preferably 1.8 to 1.85.
[0047] When the deposition layer 13 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer can be determined by X-ray photoelectron spectroscopy (XPS). For example, the measurement can be performed using an X-ray photoelectron spectrometer (manufactured by JEOL Ltd., product name: JPS-90MXV) as a measuring device, a non-monochromated MgKα (1253.6 eV) X-ray source, and an X-ray output of 100 W (10 kV-10 mA). For quantitative analysis to determine the O / Si ratio, relative sensitivity factors of 2.28 for O1s and 0.9 for Si2p can be used.
[0048] The thickness of the deposition layer 13 is, for example, 5 nm or more and 80 nm or less. When the thickness of the deposition layer 13 is 5 nm or more, sufficient water vapor barrier properties can be obtained. When the thickness of the deposition layer 13 is 80 nm or less, the occurrence of cracks due to deformation caused by internal stress of the thin film can be suppressed, and the deterioration of water vapor barrier properties can be suppressed. Note that, when the thickness of the deposition layer 13 exceeds 80 nm, costs tend to increase due to an increase in the amount of material used and a prolonged film formation time, and this is not preferable from an economical point of view. From the same viewpoint as above, the thickness of the deposition layer 13 may be 20 nm or more and 40 nm or less.
[0049] The deposition layer 13 can be formed by, for example, vacuum film formation. In the vacuum film formation, physical vapor deposition or chemical vapor deposition can be used. Examples of physical vapor deposition include, but are not limited to, vacuum deposition, sputtering, and ion plating. Examples of chemical vapor deposition include, but are not limited to, thermal CVD, plasma CVD, and photo CVD.
[0050] In the vacuum film formation, resistance heating vacuum deposition, EB (Electron Beam) heating vacuum deposition, induction heating vacuum deposition, sputtering, reactive sputtering, dual magnetron sputtering, plasma enhanced chemical vapor deposition (PECVD), etc. are particularly preferably used. However, in terms of productivity, the vacuum deposition is currently the most superior. As a heating means for the vacuum deposition, any of the electron beam heating method, resistance heating method, and induction heating method may be used.
[0051] [Barrier Coat 14] The barrier coat 14 is a coating layer having gas barrier properties (gas barrier coating layer) and is provided on the substrate 11. The barrier coat 14 is a layer formed using a composition for forming a gas barrier coating layer (hereinafter also referred to as a coating agent) containing at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide, a silane coupling agent, and hydrolysates thereof, for example.
[0052] From the viewpoint of more fully maintaining the gas barrier property after hot water treatment such as retort treatment, the coating agent preferably contains at least a silane coupling agent or a hydrolyzate thereof, more preferably contains at least one selected from the group consisting of a hydroxyl group-containing polymer compound, a metal alkoxide and their hydrolyzates, and a silane coupling agent or a hydrolyzate thereof, and further preferably contains a hydroxyl group-containing polymer compound or a hydrolyzate thereof, a metal alkoxide or a hydrolyzate thereof, and a silane coupling agent or a hydrolyzate thereof. The coating agent can be prepared, for example, by mixing a metal alkoxide and a silane coupling agent directly or after being previously hydrolyzed, into a solution in which a hydroxyl group-containing polymer compound, which is a water-soluble polymer, is dissolved in an aqueous (water or water / alcohol mixture) solvent.
[0053] A detailed description will be given of each component contained in the coating agent for forming the barrier coat 14. Examples of hydroxyl-containing polymer compounds used in the coating agent include polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among these, polyvinyl alcohol (PVA) is preferably used in the coating agent for the barrier coat 14 because it has particularly excellent gas barrier properties.
[0054] From the viewpoint of obtaining excellent gas barrier properties, the barrier coat 14 is preferably formed from a composition containing at least one selected from the group consisting of metal alkoxides represented by the following general formula (I) and hydrolysates thereof. M(OR 1 ) m (R 2 ) n-m …(I) In the above general formula (I), R 1 and R 2 are each independently a monovalent organic group having 1 to 8 carbon atoms, and are preferably an alkyl group such as a methyl group or an ethyl group. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 or R 2 If there are multiple, R 1 R 2 They may be the same or different.
[0055] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC2H5)4], triisopropoxyaluminum [Al(O-2'-C3H7)3], etc. Tetraethoxysilane and triisopropoxyaluminum are preferred because they are relatively stable in aqueous solvents after hydrolysis.
[0056] The silane coupling agent includes a compound represented by the following general formula (II). Si(OR 11 ) p (R 12 ) 3-p R 13…(II) In the above general formula (II), R 11 represents an alkyl group such as a methyl group or an ethyl group, and R 12 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted with an acryloxy group, or an alkyl group substituted with a methacryloxy group, and R 13 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 11 or R 12 If there are multiple, R 11 R 12 R may be the same or different. 13 Examples of the monovalent organic functional group represented by the formula (I) include a monovalent organic functional group containing a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, or an isocyanate group.
[0057] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.
[0058] The silane coupling agent may also be a polymer formed by polymerizing the compound represented by the general formula (II). The polymer is preferably a trimer, more preferably 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate. This is a condensation polymer of 3-isocyanate alkylalkoxysilane. It is known that the isocyanate moiety of this 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is chemically non-reactive, but the reactivity is ensured by the polarity of the nurate moiety. In general, it is added to adhesives, etc., in the same manner as 3-isocyanate alkylalkoxysilane, and is known as an adhesion improver. Therefore, by adding 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate to a hydroxyl group-containing polymer compound, the water resistance of the gas barrier coating layer can be improved by hydrogen bonding. 3-isocyanate alkyl alkoxysilanes are highly reactive and have low liquid stability, whereas 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates are not water-soluble due to the polarity of the nurate moiety, but are easily dispersed in aqueous solutions and can maintain a stable liquid viscosity. In addition, the water resistance of 3-isocyanate alkyl alkoxysilanes is equivalent to that of 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurates.
[0059] 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate may be produced by thermal condensation of 3-isocyanatepropylalkoxysilane, and may contain the raw material 3-isocyanatepropylalkoxysilane, but this does not cause any problem. More preferably, 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate is used, and more preferably, 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is used. This methoxy group has a fast hydrolysis rate, and those containing a propyl group are relatively inexpensive and therefore 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is advantageous in practical use.
[0060] Furthermore, known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity adjuster, and a colorant can be added to the coating agent as needed, provided that the gas barrier properties are not impaired.
[0061] The thickness of the barrier coat 14 may be 50 to 1000 nm, or 100 to 500 nm. If the thickness of the barrier coat 14 is 50 nm or more, there is a tendency that more sufficient gas barrier properties can be obtained, and if it is 1000 nm or less, there is a tendency that sufficient flexibility can be maintained.
[0062] The coating liquid for forming the barrier coat 14 can be applied by, for example, dipping, roll coating, gravure coating, reverse gravure coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset, etc. The coating film obtained by applying this coating liquid can be dried by, for example, hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, or a combination thereof.
[0063] The temperature for drying the coating film may be, for example, 50 to 150° C. or 70 to 100° C. By keeping the drying temperature within the above range, the occurrence of cracks in the deposition layer 13 and the barrier coat 14 can be further suppressed, and excellent barrier properties can be exhibited.
[0064] The barrier coat 14 may be formed using a coating agent containing a polyvinyl alcohol resin and a silane compound. If necessary, an acid catalyst, an alkali catalyst, a photopolymerization initiator, etc. may be added to the coating agent.
[0065] The polyvinyl alcohol resin is as described above. Examples of the silane compound include a silane coupling agent, polysilazane, and siloxane, and more specifically, examples of the silane compound include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.
[0066] [Print layer] The laminate 1 may have a printing layer. The printing layer can be provided, for example, on at least one surface of the substrate 11. The printing layer is provided at a position visible from the outside of the laminate 1 for the purpose of displaying information about the contents, identifying the contents, improving concealment, or improving the design of the packaging bag. The printing method and printing ink are not particularly limited, and are appropriately selected from known printing methods and printing inks in consideration of printability on the film, design such as color tone, adhesion, safety as a food container, and the like. Examples of printing methods that can be used include gravure printing, offset printing, gravure offset printing, flexographic printing, and inkjet printing. Among them, gravure printing can be preferably used from the viewpoints of productivity and high definition of the image.
[0067] In order to improve the adhesion of the printed layer, the surface of the layer on which the printed layer is to be formed may be subjected to various pretreatments such as corona treatment, plasma treatment, and frame treatment, or a coating layer such as an easy-adhesion layer may be provided.
[0068] [Sealant layer 20] The sealant layer 20 is a layer that provides heat sealing to the laminate 1, and overlaps the first main surface 10b of the barrier layer 10. From the viewpoint of recycling suitability of the laminate 1, the sealant layer 20 is a polyolefin film similar to the base material 11. In this embodiment, the sealant layer 20 has a single-layer structure and is a resin layer mainly made of polypropylene, but is not limited thereto. The sealant layer 20 may have a laminate structure. The sealant layer 20 may include a polypropylene film or may be made of a polypropylene film.
[0069] The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene with an unsaturated carboxylic acid, an acid anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. As the polypropylene, a polypropylene-based resin such as homopolypropylene resin (PP), propylene-ethylene random copolymer (random PP), propylene-ethylene block copolymer (block PP), propylene-α-olefin copolymer, or the like may be used. In one example, when the sealant layer 20 has a laminated structure, the sealant layer 20 has at least one of a layer containing a homopropylene resin, a layer containing random PP, a layer containing block PP, and a layer containing a propylene-α-olefin copolymer. From the viewpoint of the shape stability of the sealant layer 20, a layer containing block PP may be used as an intermediate layer of the sealant layer 20. In this case, an elastomer may be added to the intermediate layer. From the viewpoint of the elastic modulus of the sealant layer 20 described later, the amount of the elastomer added is, for example, 10% by mass or more and 30% by mass or less. From the viewpoint of the sealing function of the sealant layer 20, the front and back surfaces of the sealant layer 20 may be constituted by layers containing random PP.
[0070] The polypropylene film constituting the sealant layer 20 may be a non-oriented polypropylene film from the viewpoint of improving the sealing property by heat sealing.
[0071] The polypropylene film constituting the sealant layer 20 may contain various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent.
[0072] The thickness of the sealant layer 20 is determined depending on the weight of the contents, the shape of the packaging bag, etc., but may be approximately 30 to 150 μm, or may be 50 to 80 μm.
[0073] From the viewpoint of the opening property of a packaging bag when the laminate 1 is used to form the packaging bag, the elastic modulus of the sealant layer is, for example, 600 MPa or more, 700 MPa or more, 850 MPa or more, etc. The elastic modulus of the sealant layer 20 along the MD direction of the substrate 11 and the elastic modulus of the sealant layer 20 along the TD direction of the substrate 11 are, for example, 600 MPa or more. In one example, the elastic modulus of the sealant layer 20 along the MD direction of the substrate 11 is 850 MPa or more, and the elastic modulus of the sealant layer 20 along the TD direction of the substrate 11 is 700 MPa or more. From the viewpoint of the adhesion between the sealant layers 20, the elastic modulus of the sealant layer is, for example, 1400 MPa or less, 1100 MPa or less, 1000 MPa or less, etc. The elastic modulus of the sealant layer 20 along the MD direction of the substrate 11 is 1100 MPa or less, and the elastic modulus of the sealant layer 20 along the TD direction of the substrate 11 is 1000 MPa or less. In one example, the elastic modulus of the sealant layer is 600 MPa or more and 1400 MPa or less. In this embodiment, the elastic modulus of the sealant layer 20 is calculated from the stress measured when a 20 mm square sample of the sealant layer 20 is stretched by 0.05% to 0.25% under the conditions of a gauge length of 250 mm and a tensile speed of 5 m / min. The openability of the packaging bag corresponds to the ease of opening the bag. When the openingability of the packaging bag is good, the packaging bag is less likely to fail when filling the content.
[0074] The sealant layer 20 can be formed by any of the known lamination methods, such as a dry lamination method in which a film-like sealant layer made of the above-mentioned polypropylene is bonded with an adhesive such as a one-component curing or two-component curing urethane adhesive, a non-solvent dry lamination method in which a film-like sealant layer is bonded with a solvent-free adhesive, and an extrusion lamination method in which the above-mentioned polypropylene is heated and melted, extruded into a curtain shape, and bonded together.
[0075] Among the above-mentioned forming methods, the dry lamination method is preferred because it has high resistance to retort treatment, particularly high-temperature hot water treatment at 120° C. or higher. On the other hand, if the packaging bag is used for an application in which it is treated at a temperature of 85° C. or lower, the lamination method is not particularly limited.
[0076] [First adhesive layer 30] The first adhesive layer 30 is a layered member that bonds the barrier layer 10 and the sealant layer 20. For example, polyester-isocyanate resin, urethane resin, polyether resin, etc. can be used as the adhesive material contained in the first adhesive layer 30. From the viewpoint of using the packaging bag for retort applications, a urethane resin that is resistant to retort (for example, a two-liquid curing urethane adhesive) may be used as the first adhesive layer 30. From the viewpoint of environmental consideration, the adhesive may not contain 3-glycidyloxypropyltrimethoxysilane (GPTMS). The first adhesive layer 30 may not contain chlorine. In this case, the adhesive forming the first adhesive layer 30 can suppress coloring of the recycled resin after recycling and the generation of odor due to heat treatment. From the viewpoint of environmental consideration, the first adhesive layer 30 may be formed of a biomass material and may not contain a solvent.
[0077] When a two-liquid curing urethane adhesive is used as the first adhesive layer 30, the urethane adhesive is formed of a base agent and a curing agent. The base agent is, for example, polyester polyol, polyester polyurethane polyol, etc. The polyester polyol is obtained by polymerizing, for example, a diol and a dicarboxylic acid. The polyester polyurethane polyol is obtained by polymerizing a diol, a dicarboxylic acid, and a diisocyanate. The diol is, for example, ethylene glycol, neopentyl glycol, 1,6-hexanediol, 2,4-hexylene glycol, etc. The dicarboxylic acid is, for example, adipic acid, sebacic acid, isophthalic acid, terephthalic acid, etc. The diisocyanate is, for example, isophorone diisocyanate (hereinafter, referred to as IPDI). Examples of the curing agent include an adduct of IPDI with trimethylolpropane (hereinafter referred to as TMP), an adduct of xylylene diisocyanate (hereinafter referred to as XDI) with TMP, a mixture of an adduct of IPDI with TMP and an adduct of XDI with TMP, a biuret of hexamethylene diisocyanate (hereinafter referred to as HDI), etc. The weight-average molecular weight (Mw) of the urethane adhesive is not particularly limited, but is, for example, about 10,000 to 50,000.
[0078] The thickness of the first adhesive layer 30 is 0.5 μm or more and 10 μm or less. When the thickness of the first adhesive layer 30 is 0.5 μm or more, peeling between the barrier layer 10 and the sealant layer 20 can be effectively suppressed. When the thickness of the first adhesive layer 30 is 10 μm or less, the laminate 1 can be easily made into a mono-material (details will be described later). The thickness of the first adhesive layer 30 may be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.
[0079] [Elastic modulus of first adhesive layer 30] In this embodiment, after the retort treatment is performed on the laminate 1, the elastic modulus of the first adhesive layer 30 is 5 MPa or more and less than 53 MPa. In this case, the first adhesive layer 30 can well follow the expansion and contraction of the base material 11 accompanying the heating treatment such as the retort treatment and the boiling treatment. Therefore, even if the above-mentioned heating treatment is performed on the laminate 1 including the base material 11 having the above-mentioned thermal shrinkage rate, peeling between the barrier layer 10 and the sealant layer 20 is unlikely to occur. In addition, the occurrence of cracks in the first adhesive layer 30 during cooling after the above-mentioned heating treatment, and the occurrence of damage to the barrier layer 10 (at least one of the adhesion layer 12, the deposition layer 13, and the barrier coat 14) accompanying the occurrence of the cracks are suppressed. The elastic modulus of the first adhesive layer 30 after the retort treatment may be, for example, 9 MPa or more, 15 MPa or more, 20 MPa or more, 50 MPa or less, 47 MPa or less, or 42 MPa or less. The elastic modulus of the first adhesive layer 30 before the retort treatment of the laminate 1 is not particularly limited, but is, for example, 55 MPa or more, or 60 MPa or more.
[0080] The elastic modulus of the first adhesive layer 30 in the laminate 1 is obtained, for example, by measuring the elastic modulus of a cross section of a portion (exposed portion) exposed from the sealant layer 20. The elastic modulus of the cross section is obtained, for example, by measurement with a scanning probe microscope (SPM). In this case, the elastic modulus of the first adhesive layer 30 represents, for example, an elastic modulus calculated from a force curve measured with a scanning probe microscope (SPM). The elastic modulus of the first adhesive layer 30 is obtained, for example, by the method described in the following examples. The elastic modulus of the first adhesive layer 30 that has not been subjected to retort treatment is also obtained by the method described in the following examples.
[0081] The hardness of the adhesive layer can be controlled by the adhesive material, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer tends to be. The bulkier the adhesive, the softer the adhesive layer tends to be. The hardness of an aliphatic adhesive layer tends to be softer than that of an alicyclic or aromatic adhesive layer. The hardness of an alicyclic adhesive layer tends to be harder than that of an aromatic adhesive layer. The greater the amount of curing agent contained in the adhesive layer, the harder the adhesive layer tends to be. The longer the aging time, the harder the adhesive layer tends to be. The harder the adhesive layer, the higher the elastic modulus of the adhesive layer.
[0082] [Support layer 40] The support layer 40 is a sheet-like plastic member that functions as a support in the laminate 1. The support layer 40 may have the same function and performance as the substrate 11. The thickness of the support layer 40 may be approximately the same as the thickness of the substrate 11. From the viewpoint of recycling suitability of the laminate 1, the support layer 40 is, for example, a polyolefin film. From the viewpoint of heat resistance, the support layer 40 may include a polypropylene film or may be made of a polypropylene film. Various additives such as a flame retardant, a slip agent, an antiblocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent may be added to the polypropylene film constituting the support layer 40. The polypropylene film constituting the support layer 40 may be a stretched film or a non-stretched film.
[0083] In this embodiment, after the support layer 40 is exposed to 120°C for 15 minutes, the heat shrinkage rate in the MD direction of the support layer 40 calculated by the above formula (1) is 1% or more. For example, after the support layer 40 or a laminate of the support layer 40 and the barrier layer 10 is heated in an oven at 120°C for 15 minutes, the heat shrinkage rate in the MD direction of the support layer 40 calculated by the above formula (1) is 1% or more. The heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less. In one example, the heat shrinkage rate in the MD direction is 1.2% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, etc. The heat shrinkage rate in the MD direction is, for example, 1% or more and 7% or less, 1% or more and 6.7% or less, 1.5% or more and 4% or less, 2% or more and 3.7% or less, etc.
[0084] After the heating, the thermal shrinkage rate of the support layer 40 in the TD direction calculated by the formula (2) is not particularly limited, but is, for example, 1% to 12%. In one example, the thermal shrinkage rate in the TD direction is 1.2% or more, 1.5% or more, 2% or more, 2.5% or more, 3% or more, etc. The thermal shrinkage rate in the TD direction is, for example, 1% to 7%, 1% to 6.7%, 1.5% to 4%, 2% to 3.7%, etc.
[0085] [Second adhesive layer 50] The second adhesive layer 50 is a layered member that bonds the barrier layer 10 and the support layer 40. The adhesive material contained in the second adhesive layer 50 is the same as the adhesive material contained in the first adhesive layer 30. From the viewpoint of using the packaging bag for retort applications, a urethane resin having retort resistance (for example, a two-component curing urethane adhesive) may be used as the second adhesive layer 50. The thickness of the second adhesive layer 50 is the same as that of the first adhesive layer 30, and is 0.5 μm or more and 10 μm or less.
[0086] [Elastic modulus of second adhesive layer 50] In this embodiment, after the retort treatment is performed on the laminate 1, the elastic modulus of the second adhesive layer 50 is 5 MPa or more and less than 53 MPa. In this case, the second adhesive layer 50 can well follow the expansion and contraction of the base material 11 and the support layer 40 accompanying the heating treatment such as the retort treatment and the boiling treatment. Therefore, even if the above-mentioned heating treatment is performed on the laminate 1 including the base material 11 and the support layer 40 having the above-mentioned thermal shrinkage rate, peeling between the barrier layer 10 and the support layer 40 is unlikely to occur. In addition, the occurrence of cracks in the second adhesive layer 50 during cooling after the above-mentioned heating treatment, and the occurrence of damage to the barrier layer 10 (at least one of the adhesion layer 12, the deposition layer 13, and the barrier coat 14) associated with the occurrence of the cracks are suppressed. The elastic modulus of the second adhesive layer 50 after the retort treatment may be, for example, 9 MPa or more, 15 MPa or more, 20 MPa or more, 50 MPa or less, 47 MPa or less, or 42 MPa or less. The elastic modulus of the second adhesive layer 50 before the retort treatment is not particularly limited, but is, for example, 55 MPa or more or 60 MPa or more. The elastic modulus of the second adhesive layer 50 before the retort treatment is also obtained by the method described in the following examples.
[0087] The hardness of the adhesive layer can be controlled by the adhesive material, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer tends to be. The bulkier the adhesive, the softer the adhesive layer tends to be. The hardness of an aliphatic adhesive layer tends to be softer than that of an alicyclic or aromatic adhesive layer. The hardness of an alicyclic adhesive layer tends to be harder than that of an aromatic adhesive layer. The greater the amount of curing agent contained in the adhesive layer, the harder the adhesive layer tends to be. The longer the aging time, the harder the adhesive layer tends to be. The harder the adhesive layer, the higher the elastic modulus of the adhesive layer.
[0088] [Polyolefin content] The total mass ratio of polyolefin (polypropylene in this embodiment) in the laminate 1 is 90 mass% or more. This allows the laminate 1 to be said to be a packaging material made of a single material (mono-material), and has excellent recyclability. From the viewpoint of further improving recyclability, the content of polyolefin in the laminate 1 may be 92.5 mass% or more, or may be 95 mass% or more, based on the total amount of the laminate 1.
[0089] <Packaging bag> An example of a packaging bag made from the laminate 1 will be described below with reference to Fig. 3. Fig. 3 is a schematic plan view of an example of a packaging bag. The packaging bag 100 shown in Fig. 3 is formed into a bag shape by, for example, sealing the ends of the laminate 1 that has been folded in half to sandwich the contents therebetween.
[0090] The packaging bag 100 is a three-sided bag having a main body 101 in which the contents are accommodated, a sealed portion 102 located at an end of the main body 101, and a folded portion 103 in which the laminate 1 is folded. The shape of the main body 101 is not particularly limited, and may be rectangular when viewed from a predetermined direction. At least a part of the outer surface of the main body 101 may be printed. The main body 101 may accommodate a specific gas such as nitrogen in addition to the contents. The sealed portion 102 is a portion where a part of the sealant layer 20 of the laminate 1 and another part are bonded together. In the sealed portion 102, a part of the sealant layer 20 of the laminate 1 and another part are in close contact with each other. The sealed portion 102 is formed, for example, by heating and compressing (i.e., heat sealing) a part of the sealant layer 20 of the laminate 1 and another part, but is not limited thereto. For example, the sealed portion 102 may be formed by cold sealing or the like. In the packaging bag 100, the folded portion 103 forms one side of the main body portion 101, and the sealed portion 102 forms the remaining three sides of the main body portion 101. Both ends of the folded portion 103 and the sealed portion 102 overlap with each other.
[0091] After performing retort treatment on the laminate 1 according to the present embodiment described above, the elastic modulus of the first adhesive layer 30 measured by a scanning probe microscope (SPM) is 5 MPa or more and less than 53 MPa. As a result, even if the base material 11 expands and contracts due to the retort treatment, the first adhesive layer 30 follows suit well. Therefore, even if the base material 11 having a thermal shrinkage rate of 1% or more in the MD direction is included in the laminate 1, damage to the barrier coat 14 due to cracks in the first adhesive layer 30 can be suppressed. Therefore, it is possible to provide a laminate 1 that can exhibit good gas barrier properties (particularly, oxygen permeation prevention performance) even after the retort treatment.
[0092] In this embodiment, the second adhesive layer 50 contains a two-component curing urethane adhesive, and the modulus of elasticity of the second adhesive layer 50 measured by a scanning probe microscope after performing retort treatment on the laminate 1 is 5 MPa or more and less than 53 MPa. In this case, even if the base material 11 and the support layer 40 expand and contract due to the retort treatment, not only the first adhesive layer 30 but also the second adhesive layer 50 will follow suit well. Therefore, damage to the barrier coat 14 due to cracks in the second adhesive layer 50 can also be suppressed.
[0093] In this embodiment, the barrier layer 10 has an adhesion layer 12 and a deposition layer 13 located between the substrate 11 and the barrier coat 14, and the adhesion layer 12 is located between the substrate 11 and the deposition layer 13. Therefore, the gas barrier property of the laminate 1 can be improved compared to when the barrier layer has only the substrate 11 and the barrier coat 14.
[0094] In this embodiment, the thickness of the vapor-deposited layer 13 may be 5 nm or more and 80 nm or less. In this case, the gas barrier properties can be improved while preventing cracks in the vapor-deposited layer 13.
[0095] In this embodiment, the thickness of the first adhesive layer 30 may be 0.5 μm or more and 10 μm or less. In this case, peeling between the barrier layer 10 and the sealant layer 20 can be effectively suppressed, and the laminate 1 can be easily made into a mono-material.
[0096] In this embodiment, each of the substrate 11 and the sealant layer 20 is a polyolefin film, and the total mass ratio of polyolefin in the laminate 1 may be 90 mass % or more. In this case, a mono-material structure is realized.
[0097] In this embodiment, the substrate 11 may be a stretched polypropylene film, and the sealant layer 20 may be a non-stretched polypropylene film. In this case, the laminate 1 has excellent heat resistance against retort treatment and the like.
[0098] A gas barrier laminate and a packaging bag thereof according to one aspect of the present disclosure are as described in, for example, [1] to
[10] below, and have been described in detail based on the above embodiment and the above modified examples. [1] A barrier layer having a substrate on which a barrier coat is provided; a sealant layer overlying the first major surface of the barrier layer; and a support layer overlying the second major surface of the barrier layer; and a first adhesive layer that adheres the barrier layer and the sealant layer; a second adhesive layer that adheres the barrier layer and the support layer; A gas barrier laminate comprising: The first adhesive layer includes a two-component curing urethane adhesive, The substrate comprises a polyolefin; After performing a retort treatment on the gas barrier laminate, the elastic modulus of the first adhesive layer measured by a scanning probe microscope is 5 MPa or more and less than 53 MPa. Gas barrier laminate. [2] The second adhesive layer contains a two-component curing urethane adhesive, The gas barrier laminate according to [1], wherein the elastic modulus of the second adhesive layer measured by a scanning probe microscope after the retort treatment is 5 MPa or more and less than 53 MPa. [3] The barrier layer further comprises an anchor coat layer and a deposition layer located between the substrate and the barrier coat; The gas barrier laminate according to [1] or [2], wherein the anchor coat layer is located between the substrate and the deposition layer. [4] The gas barrier laminate according to [3], wherein the thickness of the vapor deposition layer is 5 nm or more and 80 nm or less. [5] The gas barrier laminate according to any one of [1] to [4], wherein the first adhesive layer has an elastic modulus of 55 MPa or more as measured by a scanning probe microscope before the retort treatment. [6] The gas barrier laminate according to any one of [1] to [5], wherein the first adhesive layer and the second adhesive layer each have a thickness of 0.5 μm or more and 10 μm or less. [7] The gas barrier laminate according to any one of [1] to [6], wherein the elastic modulus of the sealant layer is 600 MPa or more and 1400 MPa or less. [8] Each of the substrate and the sealant layer is a polyolefin film; The gas barrier laminate according to any one of [1] to [7], wherein the total mass proportion of the polyolefin in the gas barrier laminate is 90 mass % or more. [9] The substrate is a stretched polypropylene film; The gas barrier laminate according to [8], wherein the sealant layer is a non-oriented polypropylene film.
[10] A packaging bag made of the gas barrier laminate according to any one of [1] to [9].
[0099] However, one aspect of the present disclosure is not limited to the above embodiment, the above modified example, and the above items [1] to
[10] . One aspect of the present disclosure can be further modified without departing from the gist of the present disclosure.
[0100] In the above embodiment and the above modification, the total mass ratio of polypropylene in the laminate may be 90 mass% or more. Therefore, for example, in the laminate according to the above modification, the mass ratio of polypropylene in one of the base material and the support layer may be less than 90 mass%. Alternatively, in the laminate, the mass ratio of polypropylene in the barrier layer may be less than 90 mass%.
[0101] In the above embodiment and the above modification, the anchor coat layer and the deposition layer are provided on the substrate, but the present invention is not limited thereto. For example, the deposition layer may be provided on the sealant layer. In this case, the anchor coat layer may be provided between the sealant layer and the deposition layer. In this case, the sealant layer and the anchor coat layer may be coextrusion layers. Alternatively, the anchor coat layer and the deposition layer may be included on the substrate, and the deposition layer may be provided on the sealant layer. EXAMPLES
[0102] The present disclosure will be described in more detail with reference to the following examples, but the present disclosure is not limited to these examples.
[0103] <Substrate, supporting layer and sealant layer> As one combination of the substrate and the support layer (first combination), a biaxially oriented polypropylene (OPP) film (manufactured by Mitsui Chemicals Tohcello Co., Ltd., product name: ME-1, MD heat shrinkage rate: 2.0%, thickness: 20 μm) was prepared. As another combination of the substrate and the support layer (second combination), a biaxially oriented polypropylene (OPP) film (MD heat shrinkage rate: 3.7%, thickness: 20 μm) was prepared. As yet another combination of the substrate and the support layer (third combination), a biaxially oriented polypropylene (OPP) film (MD heat shrinkage rate: 6.7%, thickness: 20 μm) was prepared. In addition, the following five types of sealant layers were prepared as the sealant layer. First sealant layer: non-oriented polypropylene (CPP) film (manufactured by Toray Film Processing Co., Ltd., product name: Torayfan ZK93KM, thickness: 60 μm) Second sealant layer: Polypropylene laminate film (1) (thickness: 60 μm) Third sealant layer: Polypropylene laminate film (2) (thickness: 60 μm) Fourth sealant layer: polypropylene laminate film (3) (thickness: 60 μm) Fifth sealant layer: polypropylene laminate film (4) (thickness: 60 μm)
[0104] Each of the polypropylene laminated films (1) to (4) has a three-layer structure of a surface layer (10 μm) / an intermediate layer (40 μm) / a back layer (10 μm). The surface layer and the back surface of the polypropylene laminated film (1) are each formed from a mixture (h-PP:r-PP=7:3) of homopolypropylene resin (h-PP) and propylene-ethylene random copolymer (r-PP). The surface layer and the back surface of the polypropylene laminated film (2) to (3) are each formed from r-PP. The intermediate layer of the polypropylene laminated film (1) to (4) is formed from a propylene-ethylene block copolymer (b-PP). The amount of elastomer (Tafmer PN-3560, manufactured by Mitsui Chemicals, Inc.) added to the intermediate layer of the polypropylene laminated film (1) is 31% by mass. No elastomer is added to the intermediate layer of the polypropylene laminated film (2). The amount of elastomer (Tafmer PN-3560, manufactured by Mitsui Chemicals, Inc.) added to the intermediate layer of the polypropylene laminate film (3) is 31 mass %. The amount of elastomer (Tafmer PN-3560, manufactured by Mitsui Chemicals, Inc.) added to the intermediate layer of the polypropylene laminate film (4) is 55 mass %.
[0105] <Preparation of Adhesion Layer-Forming Composition> A mixed solution was produced by mixing and stirring γ-isocyanatepropyltrimethoxysilane:acrylic polyol at a ratio of 1:5. Next, tolylene diisocyanate (TDI) was added to the mixed solution so that the number of NCO groups of tolylene diisocyanate was equal to the number of OH groups of the acrylic polyol. Then, the mixed solution was diluted with ethyl acetate to 2% by mass. This prepared a composition for forming an adhesion layer (anchor coating agent).
[0106] <Preparation of coating solution α for barrier coat> The following liquids A, B, and C were prepared in amounts of 10 g each and mixed to prepare coating liquid α. Liquid A: A hydrolysis solution with a solid content of 5 mass% (SiO2 equivalent) obtained by adding 72.1 g of 0.1N hydrochloric acid to 17.9 g of tetraethoxysilane (Si(OC2H5)4) and 10 g of methanol and stirring for 30 minutes. Liquid B: 5% by mass solution of polyvinyl alcohol in water / methanol (mass ratio of water:methanol is 95:5). Liquid C: A hydrolysis solution in which 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixture of water and isopropyl alcohol (water:isopropyl alcohol mass ratio 1:1) to a solid content of 5 mass%.
[0107] <Preparation of coating solution β for barrier coat> First, TEOS, methanol, and 0.1N hydrochloric acid were mixed in a mass ratio of 45 / 15 / 40 to obtain a TEOS hydrolysis solution. This solution, a 5 mass% aqueous solution of polyvinyl alcohol (hereinafter referred to as "PVA"), and a silane coupling agent, 1,3,5-tris(3-methoxysilylpropyl)isocyanurate, in a water / IPA (isopropyl alcohol) = 1 / 1 solution, were mixed to obtain a solid content of 5 mass% (R 2 The coating solution β was prepared by mixing the three solutions, TEOS (SiO2 solids equivalent) and isocyanurate silane (R). 2 The solution was prepared so that the mass ratio of Si(OH)3 solids (converted value) to PVA solids was 40 / 5 / 55.
[0108] <Preparation of coating solution γ for barrier coat> A coating liquid γ was prepared by mixing 40 to 75 mass % of an "aqueous polyurethane resin", 10 to 40 mass % of a "water-soluble polymer", and 5 to 20 mass % of a "silane coupling agent". Aqueous polyurethane resin: an aqueous dispersion of an aqueous polyurethane resin containing an acid group-containing polyurethane resin and a polyamine compound, an aqueous polyurethane dispersion "Takelac (registered trademark) WPB-341" manufactured by Mitsui Chemicals, Inc., with a solid content of 30%. Water-soluble polymer: polyvinyl alcohol with a saponification degree of 98 to 99% and a polymerization degree of 500 (product name: Poval PVA-105, manufactured by Kuraray Co., Ltd.). Silane coupling agent: 3-glycidoxypropyltriethoxysilane (product name: KBE-403, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0109] <Preparation of two-component curing urethane adhesives (a) to (k)> First, the following two types of polyols were prepared as base materials. Both base materials contained ethyl acetate as a solvent. Base A: A polyester polyol (molecular weight (Mw): 28,000) obtained by polymerizing equal amounts of ethylene glycol and neopentyl glycol as diols and adipic acid as dicarboxylic acid so that the molar ratio of diol to dicarboxylic acid is 1:1. Base B: Polyester polyurethane polyol (molecular weight (Mw): 27,000) obtained by polymerizing equal amounts of ethylene glycol and 1,6-hexanediol as diols and terephthalic acid as dicarboxylic acid so that the molar ratio of diol to dicarboxylic acid is 1:1.
[0110] As a curing agent, a mixture (molar ratio 1:1) of an adduct of isophorone diisocyanate (hereinafter referred to as IPDI) with trimethylolpropane (hereinafter referred to as TMP) and an adduct of xylylene diisocyanate (hereinafter referred to as XDI) with TMP was prepared. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.5, to obtain a two-liquid curing urethane adhesive (a).
[0111] A mixture of a TMP adduct of IPDI and a TMP adduct of XDI (molar ratio 1:1) was prepared as a curing agent. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (b).
[0112] A mixture of a TMP adduct of IPDI and a TMP adduct of XDI (molar ratio 2:1) was prepared as a curing agent. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.5, to obtain a two-liquid curing urethane adhesive (c).
[0113] A mixture of a TMP adduct of IPDI and a TMP adduct of XDI (molar ratio 3:1) was prepared as a curing agent. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.5, to obtain a two-liquid curing urethane adhesive (d).
[0114] A mixture of a TMP adduct of IPDI and a TMP adduct of XDI (molar ratio 3:1) was prepared as a curing agent. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (e).
[0115] A mixture of a TMP adduct of IPDI and a TMP adduct of XDI (molar ratio 3:1) was prepared as a curing agent. Next, the main component B and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (f).
[0116] A burette of hexamethylene diisocyanate (hereinafter referred to as HDI) was prepared as a curing agent. Next, the base component A and the curing agent were mixed so that the NOC / OH ratio was 1.5, to obtain a two-liquid curing urethane adhesive (g).
[0117] A burette of HDI was prepared as the curing agent. Next, the base component A and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (h).
[0118] A TMP adduct of IPDI was prepared as a curing agent. Next, the main component A and the curing agent were mixed so that the NOC / OH ratio was 1.5 to obtain a two-liquid curing urethane adhesive (i).
[0119] A TMP adduct of IPDI was prepared as a curing agent. Next, the base component A and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (j).
[0120] A TMP adduct of IPDI was prepared as a curing agent. Next, the base component B and the curing agent were mixed so that the NOC / OH ratio was 1.8, to obtain a two-liquid curing urethane adhesive (k).
[0121] Example 1 The adhesive layer forming composition was applied to the substrate using a bar coater, and the adhesive layer forming composition was dried at 50° C. This resulted in the formation of an adhesive layer (anchor coat layer) having a thickness of 0.2 μm. Next, a transparent deposition layer (silica deposition layer) made of silicon oxide having a thickness of 40 nm was formed using a vacuum deposition apparatus using an electron beam heating method.
[0122] Next, the coating liquid α was applied onto the deposition layer using a bar coater, and the coating liquid α was dried at 60° C. for 1 minute. As a result, a barrier coat having a thickness of 300 nm was formed on the deposition layer. In this manner, a barrier layer having a substrate, an adhesion layer, a deposition layer, and a barrier coat was formed.
[0123] Next, a two-component curing urethane adhesive (a) was applied onto the barrier coat of the barrier layer to form a 3 μm thick adhesive layer (second adhesive layer). Next, the support layer was laminated via the adhesive layer by a dry lamination method. Next, a two-component curing urethane adhesive (a) was applied onto the substrate of the barrier layer to form a 3 μm thick adhesive layer (first adhesive layer). Next, the first sealant layer was laminated via the adhesive layer by a dry lamination method. In this way, a laminate (gas barrier laminate) having a laminated structure of the support layer, the second adhesive layer, the barrier coat, the deposition layer, the adhesion layer, the substrate, the first adhesive layer, and the first sealant layer was produced. The polypropylene content in the obtained laminate was 90% by mass or more.
[0124] (Examples 2 to 8) Laminates of Examples 2 to 8 were produced in the same manner as in Example 1, except that two-component curing urethane adhesives (b) to (h) were used instead of the adhesive (a).
[0125] (Examples 9 to 16) The laminates of Examples 9 to 16 were produced in the same manner as in Examples 1 to 8, except that the coating liquid β was used instead of the coating liquid α.
[0126] (Examples 17 to 24) Laminates of Examples 17 to 24 were produced in the same manner as in Examples 1 to 8, except that coating liquid γ was used instead of coating liquid α.
[0127] (Examples 25 to 32) The laminates of Examples 25 to 32 were produced in the same manner as in Examples 1 to 8, except that the combination of the substrate and the support layer was the second combination, and that coating liquid β was used instead of coating liquid α.
[0128] (Examples 33 to 40) The laminates of Examples 33 to 40 were produced in the same manner as in Examples 1 to 8, except that the combination of the substrate and the support layer was the third combination, and that coating liquid β was used instead of coating liquid α.
[0129] (Examples 41 to 48) Laminates of Examples 41 to 48 were produced in the same manner as in Examples 1 to 8, except that a second sealant layer was used as the sealant layer and that coating liquid β was used instead of coating liquid α.
[0130] (Examples 49 to 56) Laminates of Examples 49 to 56 were produced in the same manner as in Examples 1 to 8, except that a third sealant layer was used as the sealant layer and that coating liquid β was used instead of coating liquid α.
[0131] (Examples 57 to 64) Laminates of Examples 57 to 64 were produced in the same manner as in Examples 1 to 8, except that a fourth sealant layer was used as the sealant layer and that coating liquid β was used instead of coating liquid α.
[0132] (Examples 65 to 72) Laminates of Examples 65 to 72 were produced in the same manner as in Examples 1 to 8, except that a fifth sealant layer was used as the sealant layer and that coating liquid β was used instead of coating liquid α.
[0133] (Examples 73 to 80) The laminates of Examples 73 to 80 were each produced in the same manner as Examples 9 to 16, except that the order of lamination was support layer, second adhesive layer, substrate, adhesion layer, vapor deposition layer, barrier coat, first adhesive layer, and the above-mentioned first sealant layer.
[0134] (Comparative Examples 1 to 3) Laminates of Comparative Examples 1 to 3 were produced in the same manner as in Example 1, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0135] (Comparative Examples 4 to 6) Laminates of Comparative Examples 4 to 6 were produced in the same manner as in Example 9, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0136] (Comparative Examples 7 to 9) Laminates of Comparative Examples 7 to 9 were produced in the same manner as in Example 17, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0137] (Comparative Examples 10 to 12) Laminates of Comparative Examples 10 to 12 were produced in the same manner as in Example 25, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0138] (Comparative Examples 13 to 15) Laminates of Comparative Examples 13 to 15 were produced in the same manner as in Example 33, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0139] (Comparative Examples 16 to 18) Laminates of Comparative Examples 16 to 18 were produced in the same manner as in Example 41, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0140] (Comparative Examples 19 to 21) Laminates of Comparative Examples 19 to 21 were produced in the same manner as in Example 49, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0141] (Comparative Examples 22 to 24) Laminates of Comparative Examples 22 to 24 were produced in the same manner as in Example 57, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0142] (Comparative Examples 25 to 27) Laminates of Comparative Examples 25 to 27 were produced in the same manner as in Example 65, except that two-component curing urethane adhesives (i) to (k) were used instead of the adhesive (a).
[0143] (Comparative Examples 28 to 30) The laminates of Comparative Examples 28 to 30 were produced in the same manner as Comparative Examples 4 to 6, except that the order of lamination was support layer, second adhesive layer, substrate, adhesion layer, vapor deposition layer, barrier coat, first adhesive layer, and the first sealant layer.
[0144] <Method for measuring the thermal shrinkage rate of substrate> The heat shrinkage of the substrate included in the barrier layer was measured according to the following procedure. The measurement results of the heat shrinkage of the substrate in Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1 below. The measurement results of the heat shrinkage of the substrate in Examples 9 to 16 and Comparative Examples 4 to 6 are shown in Table 2 below. The measurement results of the heat shrinkage of the substrate in Examples 17 to 24 and Comparative Examples 7 to 9 are shown in Table 3 below. The measurement results of the heat shrinkage of the substrate in Examples 25 to 32 and Comparative Examples 10 to 12 are shown in Table 4 below. The measurement results of the heat shrinkage of the substrate in Examples 33 to 40 and Comparative Examples 13 to 15 are shown in Table 5 below. The measurement results of the heat shrinkage of the substrate in Examples 41 to 48 and Comparative Examples 16 to 18 are shown in Table 6 below. The measurement results of the heat shrinkage of the substrate in Examples 49 to 56 and Comparative Examples 19 to 21 are shown in Table 7 below. The measurement results of the heat shrinkage of the substrate in Examples 57 to 64 and Comparative Examples 22 to 24 are shown in Table 8 below. The measurement results of the heat shrinkage ratios of the substrates in Examples 65 to 72 and Comparative Examples 25 to 27 are shown in Table 9 below. The measurement results of the heat shrinkage ratios of the substrates in Examples 73 to 80 and Comparative Examples 28 to 30 are shown in Table 10 below.
[0145] As shown in FIG. 4(a), a measurement sample 500 was prepared by cutting a single substrate to be measured into a size of 200 mm×200 mm. (b) As shown in FIG. 4, two straight lines L1 and L2, each having a length of 120 mm or more and parallel to the TD direction of the measurement sample 500, were written with an interval of 100 mm. (c) As shown in FIG. 4, two straight lines L3 and L4, each having a length of 120 mm or more and parallel to the MD direction of the measurement sample 500, were drawn with an interval of 100 mm. (d) As shown in Fig. 4, seven graduations N1 to N7 were written at 20 mm intervals on the line L1. Graduations were written similarly on the lines L2 to L4. At this time, the graduations of the lines L1 and L2 were aligned so that when the graduations N1 to N7 of the line L1 and the graduations N1 to N7 of the line L2 were connected by straight lines, the lines were parallel to the MD direction. In addition, the graduations of the lines L3 and L4 were aligned so that when the graduations N1 to N7 of the line L3 and the graduations N1 to N7 of the line L4 were connected by straight lines, the lines were parallel to the TD direction. (e) The measurement sample 500 placed on a Teflon (registered trademark) sheet was placed on a glass plate in an oven heated to a predetermined temperature (150°C or 160°C) and heated for 15 minutes. After heating, the measurement sample 500 was removed from the oven and left at room temperature (25°C) for 30 minutes. (f) The linear distance between the scale N1 (intersection of L1 and N1) of the straight line L1 and the scale N1 (intersection of L2 and N1) of the straight line L2 was measured as the MD length before and after heating, and the MD heat shrinkage was calculated by the following formula (1). Similarly, the MD heat shrinkage was calculated at each of the positions of the scales N1 to N7, and the average value of these was determined as the MD heat shrinkage of the measurement sample 500. MD heat shrinkage rate (%) = (MD length before heating - MD length after heating) / MD length before heating × 100 ... (1)
[0146] <Retort processing> Using the laminates produced in each of the Examples and Comparative Examples, packaging bags with four sealed sides were produced. The packaging bags were filled with water as the content. Then, retort sterilization was performed at 130°C for 60 minutes.
[0147] <Measurement of elastic modulus of the first adhesive layer> In each of Examples 1 to 80 and Comparative Examples 1 to 30, a laminate that was a part of the packaging bag after retort treatment was cut out. Then, a cross-sectional sample in which a cross section of the first adhesive layer was exposed from the cut-out laminate was produced by the following method.
[0148] <Cross-section sample creation> First, the front and back surfaces of the cut laminate were corona-treated. Then, the laminate was cut into strips of 2 mm x 3 mm with a razor, and the cut film pieces were embedded in resin. A visible light curing resin (Toagosei Co., Ltd., "Aronix LCR D-800") was used as the resin. The film pieces were embedded in resin, and then the resin was cured by light irradiation. After the resin was cured, the film pieces embedded in resin were fixed with an insert for SPM sample holder. Then, trimming and cross-section cutting of the fixed film pieces were performed with a glass knife at room temperature (25°C). Then, the cutting speed was set to 3 mm / s and the cutting film thickness was set to 500 nm, and the cross-section cutting was performed with a diamond knife until a mirror surface was obtained. An ultramicrotome (Leica Microsystems, EM UC7) was used as the cross-section cutting device. The cutting direction was horizontal to the interface of each layer included in the film pieces. Shape and elastic modulus measurements of the sample with the exposed cross section (cross-section sample) were performed while the sample was fixed in an insert for the SPM sample holder.
[0149] <Elasticity measurement> Next, the elastic modulus of the first adhesive layer was measured by a scanning probe microscope (SPM) using the following method. The cross-sectional sample was subjected to shape measurement and elastic modulus measurement using an SPM (scanning probe microscope). The SPM used was "JupiterXR (product name)" manufactured by Oxford Instruments. The cantilever (measurement probe) used for the SPM was "biosphere B30-FM (product name)" manufactured by nanotools (tip radius: 30 nm, spring constant: 2.8 N / m). In measuring the cross-sectional sample and calculating the elastic modulus of the first adhesive layer, the tip radius of the cantilever was referenced to the individual characteristic value of the product, and the spring constant and optical lever sensitivity of the cantilever were obtained using values obtained by the GetReal method, which is a calibration function of the SPM.
[0150] First, the shape of the cross-sectional sample was measured by scanning perpendicularly to the layer interface with the SPM AC mode (tapping mode) under the conditions of a field of view of 1 μm × 1 μm and a scanning speed of 2 Hz. Here, the center of the field of view was set to be the center of the film thickness of the cross section of the first adhesive layer. Next, the contact mode of the SPM was used to obtain a force curve (load-displacement curve) when the cantilever was pressed into the first adhesive layer and pulled out under the conditions of a maximum load of 10 nN and a test speed of 500 nm / s. A total of 100 force curves were obtained, 10 points vertically × 10 points horizontally at 100 nm intervals, within the above field of view. A force curve with a displacement of 500 nm or more was obtained by pressing and pulling the cantilever. For the cross-sectional sample, two measurements were performed at each sample level, and a total of 200 force curves were obtained. The elastic modulus of the cantilever was assumed to be 865 GPa, the Poisson's ratio was assumed to be 0.2, and the Poisson's ratio of the first adhesive layer was assumed to be 0.33.
[0151] The obtained force curve was analyzed using the elastic contact model of the JKR (Johnson-Kendall-Roberts) theory to calculate the elastic modulus of the first adhesive layer. The elastic modulus was calculated using the JKR theory by fitting analysis using SPM's analysis software with the elastic modulus of the sample, the displacement origin, and the maximum adhesive force as fitting parameters. The analysis range for each point on the force curve was set to the range starting from the load and displacement when the load first reached "(maximum load - minimum load) x 0.65 + minimum load" during the load change during pull-out after reaching the maximum load, and ending with the load and displacement when the load reached the minimum load.
[0152] Using the above procedure, the average value of the elastic modulus of 200 force curves obtained for each sample level was calculated. The measurement results of the elastic modulus of the first adhesive layer in each example and comparative example are shown in the following Tables 1 to 10. Note that in each example and comparative example, the elastic modulus of the second adhesive layer can be considered to be the same as the elastic modulus of the corresponding first adhesive layer.
[0153] (Oxygen permeability measurement) The oxygen transmission rate (OTR) of the laminate after the retort treatment was measured. The measurement was performed using an oxygen transmission rate measuring device (OX-TRAN (registered trademark) 2 / 20, manufactured by Modern Control) under conditions of a temperature of 30°C and a relative humidity of 70%. The OTR measurement method complies with JIS K-7126, Method B (constant pressure method), and ASTM D3985-81, and the measured OTR value is expressed in units of [cc / m 2 The OTR measurement results for each Example and Comparative Example are shown in Tables 1 to 10 below.
[0154] [Table 1]
[0155] [Table 2]
[0156] [Table 3]
[0157] [Table 4]
[0158] [Table 5]
[0159] [Table 6]
[0160] [Table 7]
[0161] [Table 8]
[0162] [Table 9]
[0163] [Table 10]
[0164] As shown in Tables 1 to 3, the oxygen permeability of the examples and comparative examples using coating liquid β or coating liquid γ is lower than that of the examples and comparative examples using coating liquid α.
[0165] As shown in Tables 1 to 3, when the base material is an OPP film, the measurement result of the oxygen permeability of the laminate increases as the elastic modulus of the first adhesive layer exceeds 43 MPa. In particular, as shown in Tables 1 to 3, the oxygen permeability when the elastic modulus of the first adhesive layer is 53 MPa or more tends to increase more rapidly than the oxygen permeability when the elastic modulus of the first adhesive layer is less than 53 MPa. For example, when Example 6 is compared with Comparative Example 1, the oxygen permeability of Comparative Example 1 is 1.6 times or more that of Example 6. Also, when Example 22 is compared with Comparative Example 7, the oxygen permeability of Comparative Example 7 is 1.5 times or more that of Example 22. Also, when the elastic modulus of the first adhesive layer is less than 10 MPa, the oxygen permeability is relatively high. This is presumably due to the first adhesive layer being too soft. From the above results, it can be presumed that a laminate showing good oxygen permeability can be obtained regardless of the type of coating liquid by adjusting the elastic modulus of the first adhesive layer to an appropriate range.
[0166] <Elastic modulus of sealant layer> A 20 mm square sample was formed from each of the first sealant layer to the fifth sealant layer. Next, using a tabletop precision universal testing machine (AUTOGRAPH AGS-X 5kN manufactured by Shimadzu Corporation), the elastic modulus (elastic modulus in the MD direction and elastic modulus in the TD direction) of the first sealant layer to the fifth sealant layer was measured from the tensile stress measured when each sample was stretched by 0.05% to 0.25% under the conditions of temperature: 30°C, humidity: 70%, gauge length: 250 mm, and tensile speed: 5 m / min. The measurement results of the elastic modulus in the MD direction and the elastic modulus in the TD direction for each of the first sealant layer to the fifth sealant layer are shown in Table 11 below.
[0167] <Filling suitability> Using the laminates produced in each Example and Comparative Example, a three-sided bag was produced, leaving one short side of 95 mm x 140 mm. Next, 70 g of water was filled in a bag feeder and packaging machine, and the opening of the three-sided bag was heat sealed to produce 1,000 packaging bags. Then, it was confirmed whether the packaging bag was a good product or not by the presence or absence of water leakage from the sealed part. The filling suitability of each Example and Comparative Example was evaluated based on the following evaluation criteria. The evaluation results of each Example are shown in Table 12 below, and the evaluation results of each Comparative Example are shown in Table 13 below. [Evaluation Criteria] A: The rate of non-defective products is 98% or more. B: The rate of non-defective products is between 95% and 98% C: The rate of non-defective products is less than 95%.
[0168] <Durability evaluation of packaging bags> A three-sided bag of 95 mm x 140 mm size was produced using the laminate produced in each Example and Comparative Example. After filling this three-sided bag with 70 g of water, the three-sided bag was heat-sealed. Then, a retort sterilization treatment was performed at 128 ° C for 15 minutes to produce a test sample. In each Example and Comparative Example, 100 test samples were produced. Next, in each Example and Comparative Example, the 100 test samples were allowed to freely fall horizontally to the floor from a position 100 cm above the floor. The free fall was repeated 100 times. Then, the durability of the packaging bag was evaluated based on the survival rate of the test sample that did not burst. The durability of the packaging bag in each Example and Comparative Example was evaluated based on the following evaluation criteria. The evaluation results in each Example are shown in Table 12 below, and the evaluation results in each Comparative Example are shown in Table 13 below. [Evaluation Criteria] A: 100% survival rate B: Residual rate is 95% or more but less than 100%
[0169] [Table 11]
[0170] [Table 12]
[0171] [Table 13]
[0172] From Tables 12 and 13, the packaging bags of Examples 57 to 72 and Comparative Examples 22 to 27 had poor filling suitability compared to Examples 1 to 56, 73 to 80, etc. In particular, the packaging bags of Examples 65 to 72 and Comparative Examples 25 to 27, in which the fifth sealant layer was used, had poor filling suitability. This is presumably due in part to the fact that the fourth sealant layer had a lower MD modulus compared to the first sealant layer, and that the fifth sealant layer was too soft. The packaging bags of Examples 49 to 56 and Comparative Examples 22 to 24, in which the third sealant layer was used, had poor durability compared to Examples 1 to 48, 57 to 80, etc. This is presumably due in part to the fact that the third sealant layer was too hard. [Explanation of symbols]
[0173] Reference Signs List: 1... laminate, 10... barrier layer, 11... substrate, 12... adhesion layer, 13... deposition layer, 14... barrier coat, 20... sealant layer, 30... first adhesive layer, 40... support layer, 50... second adhesive layer.
Claims
1. a barrier layer having a substrate on which the barrier coat is provided; a sealant layer overlying the first major surface of the barrier layer; and a support layer overlying the second major surface of the barrier layer; and a first adhesive layer that adheres the barrier layer and the sealant layer; a second adhesive layer that adheres the barrier layer and the support layer; A gas barrier laminate comprising: The first adhesive layer includes a two-component curing urethane adhesive, The substrate comprises a polyolefin; After performing a retort treatment on the gas barrier laminate, the elastic modulus of the first adhesive layer measured by a scanning probe microscope is 5 MPa or more and less than 53 MPa. Gas barrier laminate.
2. The second adhesive layer includes a two-component curing urethane adhesive, The gas barrier laminate according to claim 1 , wherein the elastic modulus of the second adhesive layer measured by a scanning probe microscope after the retort treatment is 5 MPa or more and less than 53 MPa.
3. The barrier layer further comprises an anchor coat layer and a deposition layer located between the substrate and the barrier coat; The gas barrier laminate according to claim 1 or 2, wherein the anchor coat layer is located between the substrate and the deposition layer.
4. The gas barrier laminate according to claim 3 , wherein the vapor deposition layer has a thickness of 5 nm or more and 80 nm or less.
5. 3. The gas barrier laminate according to claim 1, wherein the first adhesive layer has an elastic modulus of 55 MPa or more as measured by a scanning probe microscope before the retort treatment.
6. 3. The gas barrier laminate according to claim 1, wherein the first adhesive layer and the second adhesive layer each have a thickness of 0.5 μm or more and 10 μm or less.
7. 3. The gas barrier laminate according to claim 1, wherein the sealant layer has an elastic modulus of 600 MPa or more and 1,400 MPa or less.
8. Each of the substrate and the sealant layer is a polyolefin film; 3. The gas barrier laminate according to claim 1, wherein a total mass ratio of the polyolefins in the gas barrier laminate is 90 mass% or more.
9. The substrate is a stretched polypropylene film, The gas barrier laminate according to claim 8 , wherein the sealant layer is a non-oriented polypropylene film.
10. A packaging bag, which is a bag made of the gas barrier laminate according to claim 1 or 2.
Citation Information
Patent Citations
Gas barrier resin film
JP1998029264A
Easy-to-unseal laminate and retort pouch packaging material
JP2003236972A
Low-solvent odor easily-openable gas barrier laminate using solventless adhesive, and low-solvent odor gas barrier packaging material and packaging bag comprising the laminate
JP2019217764A
Laminate and packaging bag
JP2021020391A
Laminate for packaging material and package
JP2023079681A